Bank Stock Returns and Economic Growth in Malaysia: An Empirical Analysis of Post-Consolidation Period - Lee, Kian Tek *; Chong, C. K. (Serials Publicationa, New Delhi, 2010)
There has been a revival of interest in examining the link between stock market-growth and finance-growth hypotheses. However, the existing studies do not gauge the performance of bank functioning directly on the economic performance. The study, therefore, reviews and extends the empirical analysis between bank stock returns and long-run economic growth in Malaysia. Applying autoregressive distributed lag (ARDL) model, the results suggest a strong positive and significant relationship not only between stock market excess return and economic growth, but also between bank excess return and economic growth. The study also shows that this relationship is further enhanced by the development of domestic financial system.